Pendampingan Pembuatan Asesmen Sumatif Sebagai Laporan Hasil Belajar Peserta Didik pada Komunitas Belajar Guru PAUD - Anwar, Rosyida Nurul (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2024)
PAUD teachers need to have a deep understanding of child development and be able to measure children's developmental achievements objectively. One instrument that is often used to measure children's developmental achievements is summative assessment. One of the main challenges in PAUD education is carrying out appropriate assessments to measure and report children's development holistically. This community service implementation activity aims to assist in making a summary assessment as a report on student learning outcomes at PAUD institutions. The implementation method consists of the preparation, implementation, and follow-up stages. Participants in this training are the PAUD teacher learning community in Madiun district, East Java. The results of the service implementation show that the teacher-learning community is aware of reporting student learning outcomes through summative assessments and the components therein. Able to create independently and carry out assessments. Summative assessment provides an overview and teacher feedback on students.